“New types of stories”: a narrative view of good nursing care of severely ill adult patients suffering an eating disorder - Berit Støre Brinchmann (Journal of Eating Disorders)
Abstract Background This study is based on narratives about good nursing care from nurses with experience of working with adult patients with a severe eating disorder. Its aim is to explore and elaborate on nurses` stories. What do nurses highlight as being good nursing practice, and what can we learn from their accounts of good nursing care for people with a serious eating disorder? Methods Riessman’s thematic narrative approach was chosen. Twelve nurses were interviewed individually and asked to reflect on stories from their nursing practice in which they had performed good nursing care. Four stories from these interviews were selected for this article. These four stories were analysed deductively, based on virtue ethics. The stories were worked on one at a time and then considered and analysed together toidentify differences and similarities. Results The analysis shows how nurses, in addition to scientific knowledge and experience, apply virtues, professional judgement and phronetic knowledge, and take risks in the nursing of patients with a severe eating disorder. Conclusion Stories of nurses are needed to complement the medical, psychological and diagnostic language used in the treatment of eating disorder patients and will further enrich both clinical practice and research.